A statistical insight to exploration of medicinal wastewater as a source of thermostable lipase-producing microorganisms - Sisir Rajak; Shaikh Rajesh Ali; Baidyanath Pal; Sibani Sen Chakraborty (PLoS ONE, 2025)
Bacteria are ubiquitous and capable of thriving in diverse environments, including industrial effluents, which often present harsh physical and chemical conditions. These microorganisms produce various intracellular and extracellular biomolecules that enable adaptation, tolerance, and utilization of such extreme environments. Recognizing the growing industrial demand for thermostable lipases, this study focuses on the isolation, characterization, and optimization of lipase-producing bacteria from medicinal wastewater collected from a factory in North 24 Parganas, Kolkata, West Bengal, India. Nineteen lipase-producing bacterial isolates were obtained from nutrient agar plates and screened using tributyrin agar (TBA) plates. Extracellular lipolytic activity was confirmed via the cup-plate method with Tween 20/80 agar and methyl red as the indicator. The isolates were characterized morphologically and through biochemical tests. Extracellular lipase activity was quantified spectrophotometrically using para-nitrophenyl palmitate (pNPP) as a substrate in 50 mM Tris-HCl buffer, with absorbance measured at 410 nm after incubation at 65°C for 20 minutes to assess thermostability. Of the 19 isolates, 11 produced thermolabile lipases, while 8 exhibited thermostable lipase activity. Among these, three isolates (MWS14, MWS6, and MWS18) demonstrated high thermostable lipase production, with MWS18 being the most productive. Ribotyping and BLAST analysis revealed that these isolates shared 99% sequence similarity with Enterococcus, Bacillus, and Serratia species, respectively. Statistical analysis using the Kruskal-Wallis H-test confirmed significant differences in lipase production among the three groups of isolates. The study also predicts greater lipase production potential in Gram-negative bacterial strains compared to Gram-positive isolates. These findings highlight the industrial relevance of medicinal wastewater as a source of thermostable lipase-producing bacteria.